Establishment of callus-cultures of the Argentinean mistletoe, Ligaria cuneifolia (R. et P.) Tiegh (Loranthaceae) and screening of their polyphenolic content - Ricco, María Valeria (2019)
Ligaria cuneifolia (R. et P.) Tiegh (Loranthaceae), known as liga, muérdago criollo, or Argentinean mistletoe, is a hemiparasitic plant with a broad distribution in central and northern Argentina. Pharmacological studies showed that L. cuneifolia extracts have hypolipemic, antioxidant, antibacterial, and immunomodulatory effects. We have established callus cultures from embryo and haustoria fragments. The highest frequency of callus formation from embryos (85%) was obtained on White medium with 4% (w/v) sucrose and 2.5 µM 1-naphtalene acetic acid and 9.2 µM kinetin as plant growth regulators (PGRs). From haustoria, the best result (35%) was obtained on Gamborg medium with 3% (w/v) sucrose and 0.45 µM 2,4-dichlorephenoxyacetic acid and 0.47 µM zeatin as PGRs. Thin layer chromatography showed that callus methanolic extract (2.5% w/v) had a lower content of flavonoids and proanthocyanins as compared to the wild plant (5% w/v for leaves, stems, and flowers), but a higher content of hydroxycinnamic acids. High performance liquid chromatography–tandem mass spectrometry (HPLC–MS/MS) showed the presence of quercetin glycosides and phenolic acids in the methanolic extracts both from the parent plant and the callus obtained from embryo.